2021
DOI: 10.3389/fmars.2021.769077
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reclamation on Tidal Flat Morphological Equilibrium

Abstract: Reclamation is one of the most prominent anthropogenic activities affecting tidal flat morphology and the related ecosystem service. Two representative types of reclamation are upper-flat enclosure and lower-flat enrockment. From a historical perspective, different type of reclamation was adapted in different areas in ancient China. As previous studies on reclamation are often site-specific, the reason that leads to such a difference is unclear. The intertidal dynamic equilibrium theory (DET) provides a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In contrast to previous studies on tidal flat shape and evolution, we focused on fringing tidal flats, characterized by dominant longshore currents. A substantial part of previous studies focused on the equilibrium tidal flat shape for tidal flats along open coasts (Roberts et al, 2000;Pritchard and Hogg, 2003;Friedrichs, 2011;Winterwerp et al, 2013a;Zhong and Hu, 2021). For these flats the cross-shore shape is determined by the relative contribution of waves and the crossshore current.…”
Section: Fringing Tidal Flatsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies on tidal flat shape and evolution, we focused on fringing tidal flats, characterized by dominant longshore currents. A substantial part of previous studies focused on the equilibrium tidal flat shape for tidal flats along open coasts (Roberts et al, 2000;Pritchard and Hogg, 2003;Friedrichs, 2011;Winterwerp et al, 2013a;Zhong and Hu, 2021). For these flats the cross-shore shape is determined by the relative contribution of waves and the crossshore current.…”
Section: Fringing Tidal Flatsmentioning
confidence: 99%
“…As a result, observations of the impact of a dike relocation do not exist. Using a cross-shore profile model, Zhong and Hu (2021) concluded that tidal flats become accreting and steeper when reducing the tidal flat length because the cross-channel velocity gradients become smaller. On the other hand, a reduction of the tidal flat length also reduces the gross sediment transport and therefore sediment supply.…”
Section: Dike Relocationmentioning
confidence: 99%
“…The geomorphology and sediment composition of tidal flats are controlled by hydrodynamics, sediment supply, and biological activities [1]. The area corresponding to the tidal flat is gradually decreasing [3] due to sea-level rise, land subsidence, and intensifying human activities in river basins and coastal zones, of which human activities are the main driving factor [10] causing most tidal flats in the world to experience erosion [42][43][44]. Coastal erosion generally manifests as shoreline retreat and bed erosion [13,42].…”
Section: Spatiotemporal Variations In Tidal Flat Erosion-accretion Ne...mentioning
confidence: 99%
“…To obtain the tidal-induced bottom bed shear stress, we used the same method as the original DET-ESTMORF 14 . Concerning the bottom-bed shear stress induced by wave propagation, we did not utilize the SWAN model as in the original DET-ESTMORF model to compute wave height distribution but instead calculated the along-range distribution of wave height by computing the energy loss due to bottom -bed friction 59 . The attenuation of wave energy can be described using the continuum equation for wave energy flux as follows 60 :…”
Section: Det-estmorf Modelmentioning
confidence: 99%